(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2019)
Background: The objective of the study performed were to compare the pattern of tobacco use among the students of selected public and private universities. Materials and methods: A cross-sectional comparative study was conducted on 250 students of Dhaka University and East West University who were selected by convenient non probability sampling technique by face-to-face interview using a written questionnaire which was pre-tested on small number of students of NIPSOM. During the study period (January to June 2011) data concerning socio-demographic differentials with distribution, duration and pattern of smoking, per day frequency, smoking-initiation, daily expenditure for smoking and relation of type of university to tobacco use. Results: 61.2% was male and 38.8% was female and their age ranged between 18 to 29 years. 31.6% was habituated to tobacco use. 38.4% and 24.8% were habituated of smoking in public and private university respectively. Pattern of smoking showed that 59.5% had used filter tipped cigarette and 32.91% had used plain cigarette among the smokers. The mean smoking duration was 2.2 years, per day mean frequency was 8.58 times, mean daily expenditure for smoking was Tk. 49.70 and 56.96% initiated their smoking by friends. Conclusion: There was restriction of tobacco use in private university campus, but in public university, there was no restriction. Restriction of tobacco use in campus and an effective awareness program is required to discourage the use of tobacco. JCMCTA 2019 ; 30 (1) : 16-20